The Effect of Green Intellectual Capital, External Pressure, and Effective Monitoring on Fraudulent Financial Statements - R. Rosiyana Dewi; Nadia Azka Amalina; Mohamad Hafiz Rosli (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
Introduction/Main Objectives: The purpose of this study was to examine the effect of green intellectual capital, external pressure, and effective monitoring on financial statement fraud. Background Problems: Financial statements are one of the business communication tools between companies and stakeholders. Therefore, it is expected that the quality of the financial statements presented by the company can meet the required rules. However, there are still frequent cases of financial statement fraud in Indonesia. Novelty: In this study, authors combine green intellectual capital, external pressure, and effective monitoring to determine the effect on financial statement fraud of companies operating in the banking sector listed on the Indonesia Stock Exchange during the period of 2020 – 2022. Authors used green intellectual capital whose measurements were from previous research that had referred to policy conditions in Indonesia. Research Methods: The sample was determined through purposive sampling, with a total of 137 final samples used after collecting data from financial reports/annual reports/sustainability reports. The data that has been collected is then analyzed using panel data regression to determine the effect of the independent variable on the dependent variable. Finding/Results: Based on the data processing results, green intellectual capital, including green human capital and green structural capital, external pressure, and effective monitoring does not affect financial statement fraud. Whereas, green relationship capital showed a negative effect on financial statement fraud. Conclusion: From this study, it can be concluded that with companies focusing on developing green relationship capital, it can reduce the potential for fraudulent financial statements.